The influence of flooding on underground coal mines - Van Zyl, Nicolaas Lessing (University of the Free State, 2011)
The purpose of the study is to investigate the influence of flooding on underground coal mines. Two case studies were investigated the shallow underground Klibarchan coal mine and the deep underground Usutu mine. Kilbarchan colliery is located 10 km south of Newcastle in KwaZulu/Natal. It comprises two underground sections, called Roy Point and Kilbarchan. Usutu colliery is situated just 8 km outside the town of Ermelo in Mpumalanga, close to Camden power station on the N2 road to Piet Retief. The geology of both studies lies within the Karoo Group, Ecca subgroup in the Vryheid formation. Higher precipitation at Usutu and Kilbarchan occurs in the summer months, while Kilbarchan has a higher annual rainfall of 864 mm/a compared to Usutu’s 705 mm/a. The water levels at both mines yielded interesting findings. Usutu mine is compartmentalized with walls in the underground. These walls are so strong that they function as “low pressure” seals resulting in compartmentalized underground, withstanding the huge pressures created by the recharged groundwater. This causes water levels to differ in the underground. Water levels at Kilbarchan mine vary in depth, but when plotted in metres above mean sea level (mamsl) they plot in a straight line. Regional recharge at Usutu was calculated as 5.7 % and 11.3 % at Kilbarchan. Recharge is influenced by what type of mining activity was practised in that specific area. It was concluded that recharge on opencast is between 15 to 20%, the stooped area between 10-15% and in an underground shallow mine it could be as high as 10%. Mining activity ceased in 1992 at Kilbarchan. Pumping is a common practice at flooded underground mines, because the mine needs to be filled with water on an ongoing basis. This prevents sulphate generation and the water quality from deteriorating. Pumping at Usutu is well managed and flushing started to occur in the underground with the electric conductivity improving over time. Pumping at Kilbarchan is poorly managed and over pumped. The electric conductivity over time, is not improving indicating that oxygen infiltrates the system when too much pumping occurs. Bord-and-pillar mining followed by stooping has been the main mining method. At Usutu mining activity ceased in the late 1980 and then the mine was flooded. It is finally there is concluded that an underground should be flooded as quickly as possible and then managed well. Shallow underground mines have a higher potential of contamination, because of a shorter residence time. The depth of mining, topography, mining methods, water levels, exposure to oxygen, rainfall, recharge, residence time and pumping have an influence on the effects of a flooded coal mine.

Die doel van die studie is om ondersoek intestel op die invloed wat n gevloede myn het op die ondergrond. Die twee studies wat ondersoek was is die vlak ondergrondse myn Kilbarchan en die diep ondergrondse myn Usutu. Kilbarchan myn is geleë 10 km suid van Newcastle in KwaZulu-Natal. Dit word opgedeel in twee ondergrond seksies, naamlik Roy Point en Kilbarchan. Usutu myn is geleë 8 km buite die dorp van Ermelo, naby die Camden kragstasie op die N2 pad na Piet Retief. Die gelogie van beide die studies val binne die Karoo Groep, Ecca subgroup in die Vryheid formasie. Hoe reënfal vind plaas by Usutu met n somer reënval, terwyl Kilbarchan n hoer jaarlikse reenval het van 864 mm/a in vergelyking met die 705 mm/a van Usutu. Water vlakke van beide studies het interresante bevindinge opgelewer. Usutu myn is gekomparlimentaliseerd met mure in die ondergrond. Hierdie mure is so sterk dat hulle as lae druk seels funksioneer en so die ondergrond comparlimentaliseer, die mure kan hoe druk van aanvulling weerstaan. Dit veroorsaak dat watervlakke verskil in die ondergrond. Water vlakke by Kilbarchan mag verkil in diepte, maar as dit in meter bo seespiëel getrek word le dit op n reguit lyn. Die regionale aanvulling was bereken as 5.7 % by Usutu en 11.3 % by Kilbarchan. Aanvulling word beinvloed deur waste tipe myn aktiviteit in daardie area plaasgevind het. Die gevolgtrekking is dat aanvulling op oopgroef areas tussen 15-20 % is en hoë ekstraksie areas tot 10 % kan wees. Myn aktiwiteit is gestaak in 1992 by Kilbarchan en in 1980 by Usutu. Om water tepomp by ondergrondse gevloede myne is baie algemeen, want n myn moet gevloed bly die myn goed the bestuur. Dit voorkom sulfaat generasie en die kwaliteit van die water om te verswak. By Usutu word die myn goed bestuur en daar het reeds spoeling in die ondergrond begin plaasvind deur dat die EC oor tyd verbeter. By Kilbarchan word die myn teveel gepomp and swak bestuur. Die EC oor tyd verbeter nie, die rede hiervoor is dat suurstof deur die myn getrek word oor daar teveel gepomp word. Laastens is daar opgesom dat n ondergrondse myn so vinnig as moontlik gevloed moet word and bestuur word. Vlak ondergrondse myne het n hoër potensiële risiko vir contaminasie, oor dit ‘n korter akkomodasie tyd het. Die myn diepte,topografie, myn metode,water vlakke, blootstelling tot suurstof, reënval, aanvulling, akkomodasie tyd en die pomp het n invloed op die effek van n gevloede steenkool myn.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2011
Keywords: Coal mines and mining -- Enviromental aspects; Floods; Coal mines and mining; Mine drainage; Decant; Flooding; Rainfall; Sampling; Chemistry; Mining; Opencast; Depth; Pumping; Recharge